The Development and Application of Bilingual Engineering in an Education Institution (A Case Study in RMB) - Diand Mardiana (Scope : Journal of English Language Teaching, 2020)
Teaching Speaking effectively is one of problems in the field of language teaching.  Many teachers and schools are frustated in activating students’ speaking ability. We need a research to find an appropriate teaching method and teaching strategy to handle the problem. This qualitative research was applied by using system perspective. Theoretically, system perspective is a study of system by questioning: how and why a system entirely works as it should be. The researcher will come into the system, observing how the bilingual engineering is applied. The object of the research will be focused on observing the forms of bilingual engineering and all parties’ opinion related to applying bilingual program. The researcher also did literature study as a comparative study especially related to bilingual theory. The result of the research shows that the program is success. It is shown by the good satisfaction level. Satisfaction will be able to improve school’s academic achievement. Finally, the researcher believes that the application of the bilingual program has a significant implication to the school’s overall achievement.